Alterations of gut microbiota in a mouse model with partial small intestinal obstruction - Wang, Yong; Zhang, Minzhong; Jiang, Lu; Gong, Yiming; Liu, Keqiang; Zhang, Tian (Frontiers in Microbiology, 2023)
Changes in the gut microbiota of patients with partial small intestinal obstruction (PSIO) have not been widely clarified. We aimed to explore bacterial diversity in a PSIO mouse model.A PSIO mouse model was established using male C57BL/6 mice, and feces samples from the distal ileum and ileum epithelium tissues were collected. MiSeq sequencing of the 16S rRNA gene was conducted to characterize microbiota diversity and composition. RNA sequencing for differences in transcriptomic programming of the ileum tissue was performed between the PSIO and (Control) Ctrl groups.Bacterial diversity in the PSIO group was significantly lower than that in the controls.Pseudomonadota was predominant in the feces of the PSIO group. Unclassified_Muribaculaceae (P = 0.008) and Akkermansia (P = 0.007) were more abundant in the Ctrl group than those in the PSIO group.Furthermore, Escherichia_Shigella (P = 0.008) was more predominant in the feces of the PSIO group.The Kyoto Encyclopedia of Genes and Genomes pathways related to metabolism were depleted in the PSIO group. Pathways associated with intestinal fibrosis, including extracellular matrix-receptor interaction, focal adhesion, phosphoinositide 3-kinase (PI3K)-Akt signaling pathway and transforming growth factor (TGF)-beta signaling pathway, which were enriched in ileum epithelial tissue in the PSIO group.PSIO can lead to changes in the predominant intestinal bacterial groups. Depleted functional profiles of the gut microbiota were identified in the PSIO group. Functional pathways associated with intestinal fibrosis were activated by PSIO. The potential regulation by the microbiota needs to be explored in the future.